On the origin of the biological effects of time varying magnetic fields: quantitative insights - Ravikumar K.; Roy Choudury A.N.; Dubey A.K.; Kumaran V.; Basu B. (My University, 2025)
In a number of recently published experimental studies from our research group, the positive impact of magnetic stimuli (static/pulsed) on cell functionality modulation or bactericidal effects, in vitro, has been established. In order to develop a theoretical understanding of such magnetobiological effects, the present study aimed to present two quantitative models to determine magnetic Maxwell stresses as well as pressure acting on the cell membrane, under the influence of a time varying magnetic field. The model predicts that magnetic field-induced stress on the cell/bacteria is dependent on the conductivity properties of the extracellular region, which is determined to be too low to cause any significant effect. However, the force on the cell/bacteria due to the induced electric field is more influential than that of the magnetic field, which has been used to determine the membrane tension that can cause membrane poration. With a known critical membrane tension for cells, the field parameters necessary to cause membrane rupture have been estimated. Based on the experimental results and theoretically predicted values, the field parameters can be classified into three regimes, wherein the magnetic fields cause no effect or result in biophysical stimulation or induce cell death due to membrane damage. Taken together, this work provides some quantitative insights into the impact of magnetic fields on biological systems. © 2024 The Royal Society of Chemistry.